Employment effects of green energy policies - Nico Pestel (IZA World of Labor, 2014)
Many industrial countries are replacing conventional power plants with renewable energy sources. Green energy policies might affect employment in different ways. A policy shift toward a low-carbon green economy may create new and additional "green jobs" in renewable energy sources and energy-efficiency technologies. However, this may potentially come with the crowding out of employment in other sectors. In addition, energy prices may increase owing to feed-in tariffs subsidizing renewables. The resulting burden may in turn stifle labor demand in industrial sectors and reduce the purchasing power of private households.
Keywords: J21; J23; Q43; Q48; 330; employment; energy policy; renewable energy sources; energy turnaround